만성질환이 있는 일하는 노인의 건강행위 관련요인에 관한 탐색적 연구 - 김동옥(Dong Ok Kim); 윤순녕(Soon Nyung Yun) (지역사회간호학회지, 2012)
Purpose: This study aimed to identify the health behaviors of working elderly Koreans aged 65 over and examined the socio-demographic and disease-related factors by health behaviors. Methods: This study used data obtained from the 2nd basic survey of the 2008 Korean Longitudinal Study of Ageing. We selected 381 working elderly having one or more of the diseases hypertension, diabetes, heart disease or cerebrovascular disease. Results: 78.9% out of the subjects have hypertension, 31.2% have diabetes, 12.3% have heart disease, and 6.3% have cerebrovascular disease. Compared to the health behaviors of the general elderly, the rate of the practice of regular exercise among the subjects was lower, but the smoking and drinking rate were higher. The significant variables associated with health behavior practice rates were gender, type of work, subjective health status and chronic diseases. Conclusion: The type of work of the elderly with chronic diseases was significantly associated with health behaviors. Consequently, this study found that continuous care programs for the working elderly with chronic diseases should be developed and provided as an occupational health service when the jobs are offered to them.